Alcoholic and non-alcoholic steatohepatitis - Neuman, Manuela G.; Seitz, Helmut K. (Experimental and molecular pathology, 2014)
This paper is based upon the “Charles Lieber Satellite Symposia” organized by Manuela G. Neuman at the Research Society on Alcoholism (RSA) Annual Meetings, 2013 and 2014. The present review includes pre-clinical, translational and clinical research that characterize alcoholic liver disease (ALD) and non-alcoholic steatohepatitis (NASH). In addition, a literature search in the discussed area was performed. Strong clinical and experimental evidence lead to recognition of the key toxic role of alcohol in the pathogenesis of ALD. The liver biopsy can confirm the etiology of NASH or alcoholic steatohepatitis (ASH) and assess structural alterations of cells, their organelles, as well as inflammatory activity. Three histological stages of ALD are simple steatosis, ASH, and chronic hepatitis with hepatic fibrosis or cirrhosis. These latter stages may also be associated with a number of cellular and histological changes, including the presence of Mallory's hyaline, megamitochondria, or perivenular and perisinusoidal fibrosis. Genetic polymorphisms of ethanol metabolizing enzymes such as cytochrome p450 (CYP) 2E1 activation may change the severity of ASH and NASH. Alcohol mediated hepatocarcinogenesis, immune response to alcohol in ASH, as well as the role of other risk factors such as its co-morbidities with chronic viral hepatitis in the presence or absence of human immunodeficiency virus are discussed. Dysregulation of hepatic methylation, as result of ethanol exposure, in hepatocytes transfected with hepatitis C virus (HCV), illustrates an impaired interferon signaling. The hepatotoxic effects of ethanol undermine the contribution of malnutrition to the liver injury. Dietary interventions such as micro and macronutrients, as well as changes to the microbiota are suggested. The clinical aspects of NASH, as part of metabolic syndrome in the aging population, are offered. The integrative symposia investigate different aspects of alcohol-induced liver damage and possible repair. We aim to (1) determine the immuno-pathology of alcohol-induced liver damage, (2) examine the role of genetics in the development of ASH, (3) propose diagnostic markers of ASH and NASH, (4) examine age differences, (5) develop common research tools to study alcohol-induced effects in clinical and pre-clinical studies, and (6) focus on factors that aggravate severity of organ-damage. The intention of these symposia is to advance the international profile of the biological research on alcoholism. We also wish to further our mission of leading the forum to progress the science and practice of translational research in alcoholism.